African Literature: Gender Discourse, Religious Values, and the African Worldview - Salami-Boukari, Safoura (Book collections on Project MUSE., 2012)
How do we resolve the insider/outsider interpreting conundrum? Why do readers from different parts of the world read, interpret, or understand foreign literatures the way they do? What drives peculiar critical reactions, canon formations and such issues which determine the survival of cultural productions or their continued adoption as useful bolsters for a people's self-definition or indeed self-preservation and self-determination? African Literature: Gender Discourse, Religious Values, and the African Worldview offers a series of fresh insights into most of the old ""problematics"" which use.